2020
DOI: 10.1111/add.14878
|View full text |Cite
|
Sign up to set email alerts
|

The rise in non‐fatal and fatal overdoses involving stimulants with and without opioids in the United States

Abstract: AimsTo examine trends and recent changes in non-fatal and fatal stimulant overdose rates with and without opioids to improve the descriptive characterization of the US overdose epidemic. Design Secondary analysis of non-fatal and fatal drug overdose trends, focusing on the most recent years of data available to examine rate changes by demographics (2015-16 for non-fatal and 2016-17 for fatal). Setting Non-fatal drug overdoses from the Healthcare Cost and Utilization Project's Nationwide Emergency Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 23 publications
(28 reference statements)
5
87
3
Order By: Relevance
“…The large increase in cocaine overdose rates (32.9%) might indicate potential increase in polysubstance overdose. A previous study found that in 2016, approximately 27% of nonfatal cocaine overdoses treated in EDs also involved an opioid, and cocaine-involved overdoses with an opioid reported increased 17% from 2015 to 2016, whereas cocaine-involved overdoses without an opioid decreased 14% (2). Future analyses examining drug combinations could help to determine the extent to which polysubstance use affects overdose surveillance of specific drug types.…”
Section: Discussionmentioning
confidence: 99%
“…The large increase in cocaine overdose rates (32.9%) might indicate potential increase in polysubstance overdose. A previous study found that in 2016, approximately 27% of nonfatal cocaine overdoses treated in EDs also involved an opioid, and cocaine-involved overdoses with an opioid reported increased 17% from 2015 to 2016, whereas cocaine-involved overdoses without an opioid decreased 14% (2). Future analyses examining drug combinations could help to determine the extent to which polysubstance use affects overdose surveillance of specific drug types.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, increases in overdoses were initially linked to opioid pain analgesics but shifted to illicit opioids, such as heroin and fentanyl [2,[4][5][6][7]. More recently, public health officials and healthcare providers have noted a sharp increase in overdose deaths associated with illicit synthetic substances, specifically cocaine and methamphetamines, in urban areas [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with a recent study in which authors that found that nonfatal ED visits for psychostimulant overdoses between 2015 and 2016 increased by 10.1 for those aged 0 to 14 years, 9.4 for 15to 19-year-olds, and 9.9 for 19-to 24year-olds. 22 The increasing trend in suspected stimulant overdoses could also reflect trends in fatality data, with stimulant deaths representing a growing proportion of drug overdose deaths in the United States, specifically among cocaine and psychostimulants deaths. 22,26 According to current research, the most effective treatments for addiction to methamphetamine are multifaceted behavioral therapies that include such elements as individual counseling, family education, screening, 12-step support, and extracurricular activities.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, although little is known about nonfatal heroin overdoses among youth, researchers of a recent study found that between 2015 and 2016, nonfatal psychostimulant (eg, amphetamine, MDMA) ED visits increased for 0-to 24 year-olds. 22 Timely data are essential to track sudden increases in drug exposures to facilitate an appropriate, effective, and rapid public health response. ED syndromic surveillance data collected through the Centers for Disease Control and Prevention (CDC) National Syndromic Surveillance Program (NSSP) BioSense Platform are timely and fill the data gap needed to provide information for action, with data being available for analysis within 24 to 48 hours of the visit.…”
mentioning
confidence: 99%